Bucket-Handle Tear of the Triangular Fibrocartilage Complex: Surgical Technique With Clinical and Radiologic Outcome - Darshan Kumar A. Jain, M.B.B.S., M.S. (Ortho.), F.N.B. (Hand and Microsurgery); Harshit Bhaskar Shetty, M.B.B.S., M.S. (Ortho.); Rohith Gopalakrishna Bhat, M.B.B.S., M.S. (Ortho.) (Arthroscopy Techniques)
The intricate anatomy of the triangular fibrocartilage complex and its crucial role in stabilization and load transmission make it vulnerable to injury. Various tear patterns have been studied and classified on the basis of their injury mechanisms and clinical outcomes. However, a rare pattern like the bucket-handle tear finds no mention in routine classifications, and the paucity of literature shows no consensus on its management. We hereby present a technique of repairing a bucket-handle tear by reattaching its displaced/flipped flap to the dorsal vascular limbus of the disc proper.